2004
DOI: 10.1038/sj.ijo.0802733
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular hypertrophy and QT interval in obesity and in hypertension: effects of weight loss and of normalisation of blood pressure

Abstract: BACKGROUND: Left ventricular hypertrophy (LVH) and prolonged QT interval at ECG (QTc) are common in both obesity and arterial hypertension (AH), and are risk factors for cardiovascular disease and sudden death. METHODS: We compared the frequencies of LVH (ECG criteria) and QTc in obese-AH (n ¼ 41), in normotensive obese (n ¼ 75), in lean-AH (n ¼ 30), and in lean controls (n ¼ 68) comparable for age and sex; in obese patients, LVH and QTc were evaluated under basal conditions and 1 y later, that is, after a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 56 publications
4
33
0
Order By: Relevance
“…[172][173][174] Of note, after the weight loss has ceased, the persistent effect of weight loss on blood pressure may not always be encountered. 175,176 The physician who evaluates a referred patient for hypertension should be very concerned about obese patients who admit habitual snoring, nocturnal gasping or choking, witnessed episodes of apnea, and daytime sleepiness and should consider sleep-disordered breathing. [177][178][179] …”
Section: Factors Leading To An Increase In Peripheral Vascular Resistmentioning
confidence: 99%
“…[172][173][174] Of note, after the weight loss has ceased, the persistent effect of weight loss on blood pressure may not always be encountered. 175,176 The physician who evaluates a referred patient for hypertension should be very concerned about obese patients who admit habitual snoring, nocturnal gasping or choking, witnessed episodes of apnea, and daytime sleepiness and should consider sleep-disordered breathing. [177][178][179] …”
Section: Factors Leading To An Increase In Peripheral Vascular Resistmentioning
confidence: 99%
“…[62][63][64] Of note, after the weight loss has ceased, the persistent effect of weight loss on blood pressure may not always be encountered. 65,66 …”
Section: Hypertensionmentioning
confidence: 99%
“…An abnormal ventricular repolarization, which predisposes to sudden death upon cardiac arrhythmia [3], may contribute to the increased mortality risk since obesity has been found to be associated with a high prevalence of a prolonged QT interval in electrocardiographic (ECG) recordings [4]. Furthermore, weight loss, in particular when induced by bariatric surgery, has been found to reduce QT interval (QTc) length in many studies (for overview see Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the validity of this observation has been challenged by one previous study [9] that demonstrated that the significance of QTc shortening upon weight loss gets lost when the QT interval is corrected for heart rate (HR) by using Fridericia or Framingham correction equation instead of the most commonly used Bazett equation.…”
Section: Introductionmentioning
confidence: 99%